Características quantitativas da carcaça e aspectos qualitativos da carne de ovinos alimentados com dietas contendo borra de babaçu - SOUSA, Edegleicia Alves de (2021)
The objective of this research was to evaluate the effect of the inclusion of babassu sludge on the quantitative characteristics of the carcass, the physical-chemical composition, as well as sensory analysis of sheep meat. Twenty-eight Santa Inês crossbreed lambs, castrated, with an initial weight of (20.6 ± 4.1 kg) were distributed in a completely randomized design. The experimental treatments consisted of four diets, with increasing levels (0, 5, 10, 15% of dry matter in the diet) of inclusion of babassu sludge in substitution for corn and soy. The animals were confined for 60 days, the first 10 days being used to adapt to the environment and diets. At the end of the confinement period, the animals were fasted from solids for 16 hours, and then slaughtered. Carcass evaluation was performed to obtain live weight at slaughter, hot and cold carcass weight, hot and cold carcass yield, true biological and commercial yield, fat thickness, rib eye area, weight and cut yield, physical-chemical composition and sensory analysis of meat. After the evaluation of the carcass, the Longissimus lumborum muscle of each left half carcass was removed for later determination of the hundredth composition, loss of water by dripping, loss by cooking, shear force and sensory analysis. For data analysis, regression with a 5% significance level was used. The initial weight of the animals was used as a covariate. The inclusion of babassu sludge in the diet did not influence (P> 0.05) the slaughter weight with an average value of 30.11 kg; hot and cold carcass weight with average values of 13.91 kg and 13.7 kg; hot and cold carcass yield with average values of 46.40% and 45.43%; biological yield with an average value of 57.77%; fat thickness with an average value of 1.60mm; loin eye area with an average value of 11.75cm²; cut weight and yield; physical-chemical composition and sensory analysis of meat. The addition of up to 15% of babassu sludge in partial replacement to corn and soy in the diet of sheep finished in confinement does not alter the carcass characteristics, as well as the nutritional value and sensory characteristics of the meat.